Contribution of wildlife tourism in improving local communities’ livelihood in Burunge Wildlife Management Area in Tarangire Manyara Ecosystem, Tanzania - Naza Mmbaga; Joseline Tarimo; Julius Modest (Discover Global Society)
Abstract The overall objective of this study was to assess the role of wildlife tourism in improving the livelihood of communities in Burunge Wildlife Management Area (BWMA) by focusing on the economic and the socio-cultural roles. Data were obtained through household questionnaire, focus group discussions, and key informant interviews in three study villages. The data were analyzed using the Statistical Package for Social Science (SPSS) version 26 and Microsoft Excel. The findings revealed that wildlife tourism operations in the three villages associated with BWMA have generated significant benefits. Several economic and socio-cultural livelihood indicators in the study villages were significantly impacted by wildlife tourism activities. Wildlife tourism appears to have a considerable impact on increasing household incomes, but a relatively lesser impact on reducing agricultural production, which is the economic mainstay for many households in the Babati district. In terms of socio-cultural livelihood indicator, wildlife tourism operation seem to have a significant (x2 = 191.613, df = 8, N = 117 and p < 0.0001) impact in raising the profile and fame of the villages, while having a lesser impact on the erosion of local customs and culture, as most of the villagers continue to uphold their cultural practices. These findings suggest that wildlife tourism in the WMAs can improve people's standard of living and strengthen cultural values. The study recommends full consideration of socio-economic and cultural values of the communities at individual level by the potential stakeholders including policy makers. This will enhance the achievement of sustainable conservation in WMAs and community development through wildlife tourism activities.